Pengaruh ROA, NPM dan EPS Terhadap Harga Saham Syariah Perusahaan Jakarta Islamic Index - Ahmad Ulil Albab Al Umar; Arna Asna Annisa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2021)
The movement of share prices on the Jakarta Islamic Index over the past 5 years has been very volatile. A company with a good stock price indicates that the company is performing well. The research objective is to analyze the effect of partially or simultaneously the independent variables, namely Return on Assets, Net Profit Margin and Earning Per Share, on the dependent variable, namely Sharia Stock Price and use moderation variable namely Dividend Payout Ratio. The population in this study is the companies listed on the Jakarta Islamic Index period 2016-2017. The sample selection technique used purposive sampling to produce 14 sample companies. The data analysis technique uses multiple linear regression using EViews 10. The results of this study indicate that partially Return on Assets has no significant effect on sharia stock prices, Net Profit Margin has no significant effect on sharia stock prices, and Earning Per Share has a significant effect on sharia stock prices. Simultaneously, Return On Assets, Net Profit Margin and Earning Per Share affect stock prices. The Dividend Payout Ratio was unable to moderate the effect of Return On Assets and Net Profit Margin on sharia stock prices, but the Dividend Payout Ratio was able to moderate the effect of Earning Per Share on sharia stock prices.